Introduction to Forensic Psychology : Issues and Controversies in Crime and Justice. - Arrigo, Bruce A. (Elsevier, 2004)
This book, incorporating over 35% new information, presents the debates about psychology, crime, law, and the intersections in an accessible, jargon-free fashion.